Social accountability as a tool for realization of economic and social rights - Nabwowe Kasule, Angella; Mncwabe, Nokukhanya (Initiative for Social and Economic Rights (ISER), 2016)
Social Accountability can be defined as citizens’ capacity to hold the state and service providers to account in order to make them more responsive to the needs of citizens and beneficiaries. Examples of social accountability mechanisms in Uganda include informal mechanisms, for example citizen scorecards, public media campaigns/debates, performance agreements for top district officers, client charters and community meetings on accountability (“Barazas”) and the enforcement of commitments emanating therefrom; as well as mechanisms embedded in legal or policy instruments, for example School Management Committees (SMCs), Water User Committees (WUCs) and Health Unit Management Committees (HUMCs) and the like. Participation in public processes is entrenched as a legal right in Uganda’s legal framework. Article 38 of the Constitution states that every Ugandan has the right to participate in the affairs of government and to influence government policy. Article 41 guarantees the right of access to information, which is a key prerequisite for participation. Additionally, the Local Government Act provides for democratic participation in, and control of, decision-making by the people.